Synthesis, Characterization and in vitro Antifungal Screening of Manganese(II) and Copper(II) Complexes of Hexaaza [N6] Macrocyclic Ligand (Journal of Nepal Chemical Society, 2010)
New manganese(II) and copper(II) complexes of 12-membered macrocyclic Schiffbase ligand containing thiosemicarbazone moiety have been prepared of generalcomposition [MLX2] where M = Mn(II) or Cu(II), L = 3,4,9,10–tetra-2-furanyl-1,2,5,6,8,11-hexaazacyclododeca-7,12-dithione-2,4,8,10–tetraene, X = Cl-, NO3- and NCS-. Thecomplexes have been characterized by elemental analysis, molar conductance, magneticsusceptibility measurements and spectral (IR, electronic, EPR and mass) analyses. The IRspectra of complexes suggested that ligand is coordinated to the metal ion through iminenitrogen atoms. On the basis of spectral studies, an octahedral and tetragonal geometry hasbeen assigned for Mn(II) and Cu(II) complexes, respectively. EPR spectra of polycrystallineMn(II) complexes gave an isotropic signal with g value centered around free electron gvalue. EPR spectra of Mn(II) complexes in DMSO showed hyperfine splitting containing sixlines, whereas EPR spectra of polycrystatalline Cu(II) complexes showed anisotropicsignal. Conductivity measurements support the non electrolytic nature of the complexes.Magnetic moment data suggest that reported complexes are paramagnetic and of high spintype. All the examined complexes have also been tested in vitro against a number ofpathogenic fungi. Results indicated that the complexes exhibited good antifungal activities.Keywords: Macrocyclic, octahedral, antifungal, tetragonal, anisotropic.DOI:  10.3126/jncs.v25i0.3284Journal of Nepal Chemical Society Volume 25, 2010 pp 46-52